Amine-modified waste tires for CO2 capture and resource utilization - Napatjira Jaree; Dusadee Tumnantong; Jirapong Luangchaiyaporn; Pitchapa Pittayavinai; Patchanita Thamyongkit; Benjapon Chalermsinsuwan; Sirilux Poompradub (Scientific Reports)
Abstract In this study, waste tires (WTs) were chosen to prepare an adsorbent material for carbon dioxide (CO2) capture to reduce their huge amount of waste. To improve the CO2 selectivity, the WT powder was amine-modified using tetraethylenepentamine (TEPA) or polyethyleneimine at different loading levels [2.5, 5, 10, and 15% (w/w)]. The optimum condition to develop a high-performance CO2 adsorbent material was found to be the use of 10% (w/w) TEPA-modified WT (WT10T) with a CO2 flow rate of 70 mL min−1 under ambient temperature and atmospheric pressure. Based on the kinetic study of WT10T, Avrami’s model fitted well with the experimental data, suggesting both physisorption and chemisorption of the CO2. When desorbed at 60 °C under vacuum pressure, the WT10T showed a reusability of more than 10 successive adsorption cycles. Additionally, the adsorbed CO2 in WT10T could be directly converted to value-added chemicals or fuels, such as ethylene, methane, carbon monoxide, and hydrogen, via an electrochemical reaction. Accordingly, this study shows a challenging way on how to both utilize waste materials as adsorbents and reduce the WT level from rubber industries.